Karakteristik Sensorik Cookies Sweet Potasoy dengan Substitusi Tepung Ubi Jalar Ungu (Ipomoea Batatas L. Lamb) dan Tepung Kedelai (Glisine Max) Sebagai Alternatif Makanan Selingan bagi Penyandang Diabetes Melitus Tipe 2 - Suhaema, Suhaema; Adiyasa, I Nyoman; haryani, neny (Poltekkes Kemenkes Mataram, 2024)
Background: Diabetes Mellitus (DM) is a global health issue that can lead to severe complications, including cardiovascular disease, neuropathy, and retinopathy. The rising incidence of DM is often linked to unhealthy dietary habits and lifestyle choices. Recent studies indicate that consuming foods high in soluble fiber can improve glycemic control by slowing glucose absorption. Objective: This study aims to evaluate the sensory characteristics of